A Stakeholder Approach: Ethical Business Practices and Corporate Social Responsibility a road that leads to sustainability ! - Aggarwal, Shivani (The journal of contemporary issues in business and government, 2023)
The current media statements gives us an idea that the business operation are surrounded by increasing incidents of unethical practices due to the thrust for profits without realizing the negative impact. The greater profits are given more priority neglecting the moral responsibilities towards the society, the interested parties and the environment. In recent times, we are seeing that the Corporate Social responsibility is fading in some businesses, at the same time acquiring ground in the other as they aim to make their business profitable while acting in a mature and responsible way towards the society where they are operating in. A well-ordered assessment of the present-day literature hints to the existence of a strong interrelation between ethical practices, corporate social responsibility (CSR) and better financial health. It is high time for the Multinational companies and other large firms to implement a suitable stand that is ethical in moral stance and cater to the needs of sustainable development by ensuring that all the stakeholder of the organization and the environment following the approach of triple bottom line. Corporate culture pertaining to the social, economic and environmental spheres of sustainability needs a vigilant transformation by including measures that cater the demands to keep up a sustainable planet. As a consequence of explaining how and why the assimilation of ethics in business strategy and CSR initiatives increases sustainability, the following article, taking the inputs from chosen studies, tries to contribute in a minute way to make better the possibility of the amalgamation of corporate sustainability and corporate social responsibility in their world-wide operations advancing to a more sustainable planet.